Transcriptomic Profile of Blood–Brain Barrier Remodeling in Cerebral Amyloid Angiopathy - Situ, Muyu; Citalan-Madrid, Ali Francisco; Stamatovic, Svetlana M.; Keep, Richard F.; Andjelkovic, Anuska V. (Frontiers in Cellular Neuroscience, 2022)
Cerebral amyloid angiopathy (CAA) is a small vessel disease characterized by amyloid β (Aβ) peptide deposition within the walls of medium to small caliber blood vessels, cerebral microhemorrhage and blood-brain barrier (BBB) leakage. It is commonly associated with late-stage Alzheimer’s disease. BBB dysfunction is indicated as a pathological substrate for CAA progression with hyperpermeability enhancing extravasation of plasma components and inducing neuroinflammation, further worsening BBB injury and contributing to cognitive decline. Although significant effort has been made in defining the gene mutations and risk factors involved in microvascular alterations with vascular dementia and Alzheimer disease, the intra- and intercellular pathogenic mechanisms responsible for vascular hyperpermeability are still largely unknown. The present study aimed to elucidate the transcriptional profile of the cerebral microvessels (BBB) in a murine model CAA vasculopathy in order to define potential causes and underlying mechanisms of BBB injury. A comprehensive RNA sequencing analysis was performed of CAA vasculopathy in Tg-SwDI mice at 6 and 18 months in comparison to age-matched wildtype controls to examine how age and amyloid accumulation impact the transcriptional signature of the BBB. Results indicate that Aβ has critical role in triggering brain endothelial cell and BBB dysfunction in CAA vasculopathy, causing an intense proinflammatory response, impairing oxidative metabolism, altering the coagulation status of brain endothelial cells and remodeling barrier properties. The proinflammatory response includes both adaptive and innate immunity, with pronounced induction of genes that regulate macrophage/microglial activation and chemokines/adhesion molecules that support T and B cell transmigration. Age has an important impact on the effects of Aβ, increasing the BBB injury in CAA vasculopathy. However, the early inflammation, particularly microglia/macrophage activation and mediators of B lymphocytes activity are underlying processes BBB hyperpermeability and cerebral microbleeds in the early stage of CAA vasculopathy. These findings reveal a specific profile of the CAA-associated BBB injury that leads to full progression of CAA.